Histological Analysis of Murine Ovaries and Uteruses Following Supplementation with Alpha-Tocopherol in Nicotine Injected Mice - Azmil Amirudin, Mohd; Shahrizal Sanudin, Muhammad; Shahrul Nizam Mohd Isa, Mohd; Syairah Mohd Mutalip, Siti (International Journal of Engineering and Technology, 2018)
Vitamin E can be classified into eight different lipophilic subtypes; namely alpha(Î±)-, beta(Î²)-, delta(Î´)- and gamma(Î³)-tocopherol (TOC) as well as alpha(Î±)-, beta(Î²)-, delta(Î´)- and gamma(Î³)-tocotrienol (TCT). From these isoforms, Î±-TOC has been reported to have the most promising health benefits. The purpose of this study was to determine the effect of Î±-TOC on the histological structures of murine ovaries and uteruses in nicotine-treated females. Thirty ICR female mice were divided into 5 groups (Group A â€“ E) with 6 mice each. Group A received 0.1 ml of tocopherol-stripped corn oil, group B given 0.1 ml of 0.9% normal saline, group C treated with 3 mg/kg/day of nicotine, group D treated with 60 mg/kg/day of alpha-tocopherol and group E was concurrently treated with 3 mg/kg/day of nicotine and 60 mg/kg/day of alpha-tocopherol. Following the treatments, all females were euthanized and the studied organs were collected and processed for histological analysis. Obtained results indicated that exposure to nicotine reduced the numbers of ovarian follicles and endometrium thickness (Group C). However, these adverse effects have been reduced in the group concurrently treated with nicotine and Î±-TOC (Group E). This result suggested that Î±-TOC might be able to minimize the adverse effects of nicotine in the ovaries and the uterus. Further studies are needed to confirm on these effects from the physiological aspects of the ovaries and uteruses. Â